An Analysis of The Servant Leadership Role of School Principals in Improving Teacher Discipline - Haekal, T. M.; Abdi, Dira; Idris, M. Irwan; Azmi, Khairul; Fitri, Mutia (Al-Ijtima`i: International Journal of Government and Social Science, 2025)
Enhancing teacher work discipline is a fundamental aspect of realizing effective educational quality, where a leadership style such as Servant Leadership plays a vital role. This research aims to analyze the implementation of Servant Leadership by the school principal, the contribution of work discipline to teacher professionalism, the success factors, and the obstacles related to discipline policy at SMAN 3 Peusangan. The research employed a qualitative methodology with a case study approach. Data collection techniques involved structured interviews, observation, and documentation. The findings indicate that the servant leadership of the SMAN 3 Peusangan Principal effectively enhances teacher work discipline through a humanistic approach centered on service and moral role modeling, rather than structural control. This leadership style fosters discipline stemming from teachers' intrinsic professional awareness and commitment. The strategy, which focuses on empathy, open communication, and leadership integrity, is proven to improve teacher professionalism, marked by increased responsibility, work ethics, and pedagogical performance. Despite its success, the implementation of Servant Leadership still faces significant challenges in the cultural dimension (a permissive culture and close social relationships hindering the firmness of sanctions) and the systemic dimension (limited digital facilities). This finding confirms that the success of discipline highly depends on the principal's role model and service, rather than mere regulations. The study concludes that the school principal needs to strengthen the consistency of justice and teacher participation to fully implement servant leadership and effectively overcome organizational culture barriers.